Prevalence and determinants of early onset neonatal sepsis at two selected public referral hospitals in the Northwest Ethiopia: a cross-sectional study - Tadesse Yirga Akalu; Yared Asmare Aynalem; Wondimeneh Shibabaw Shiferaw; Melaku Desta; Haile Amha; Dejen Getaneh; Bayachew Asmare; Yoseph Merkeb Alamneh (BMC, 2023)
Abstract Introduction Globally, neonatal mortality is decreasing, and road maps such as the Early Newborn Action Plan set ambitious targets for 2030. Despite this, deaths in the first weeks of life continue to rise as a percentage of total child mortality. Neonatal sepsis with early onset continues to be a significant cause of death and illness. The majority of sepsis-related deaths occur in developing nations, where the prevalence and causes of newborn sepsis are yet unknown. As a result, the goal of this study was to determine the prevalence of early-onset sepsis and identify determinant factors. Methods A cross-sectional study was conducted on 368 study participants in referral hospitals of East and West Gojjam Zones from March 1st to April 30th, 2019. Study participants were selected at random using lottery method. Face-to-face interviews with index mothers for maternal variables and neonatal record review for neonatal variables were used to collect data using a structured pretested questionnaire. Data were entered into Epidata 3.1 and then exported to STATA/SE software version 14. Finally, the logistic regression model was used for analysis. Statistical significance was declared at P < 0.05 after multivariable logistic regression. Results A total of 368 newborns and their index mothers took part in this study. The mean age of the newborns was 4.69 days (± 1.93SD). Early-onset neonatal sepsis was seen in 34% of the babies. Nulliparity (AOR: 3.3, 95% CI: 1.1-9.5), duration of labor > 18 h after rupture of membranes (AOR: 11.3, 95% CI: 3.0-41.8), gestational age of 32-37 weeks (AOR: 3.2, 95% CI: 1.2-8.5), and neonates who require resuscitation at birth (AOR: 4, 95% CI: 1.4 -11.8) were all found to be significantly associated with early-onset neonatal sepsis. Conclusion and recommendation Early-onset neonatal sepsis was found to be high in this study. Early-onset neonatal sepsis was found to be associated with maternal, obstetric, and neonatal variables. Comprehensive prevention strategies that target the identified risk factors should be implemented right away.